2021
DOI: 10.1002/ctm2.390
|View full text |Cite
|
Sign up to set email alerts
|

Deubiquitinase USP35 modulates ferroptosis in lung cancer via targeting ferroportin

Abstract: 1. USP35 is abundant in human lung cancer tissues and cell lines. 2. USP35 modulates iron homeostasis and ferroptosis in lung cancer tissues and cell lines.3. USP35 directly interacts with ferroportin and maintain its protein stability to prevent iron overload and ferroptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
84
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(86 citation statements)
references
References 66 publications
0
84
2
Order By: Relevance
“…verified that USP35 could maintain the stability of its protein by deubiquitinating FPN1, and reduce the iron disorder triggered by erastin/RSL3, thereby promoting lung cancer cell growth and tumor progression. Meanwhile, knockdown of USP35 enhanced the sensitivity of lung cancer cells to cisplatin and paclitaxel by targeting FPN1 in lung cancer ( 94 ). However, a study showed that matrix/macrophage expression of Lcn-2 was associated with tumor onset, lung metastasis, and recurrence, whereas FPN1 was not by analyzing the expression profiles of lipocalin-2 ( Lcn-2 ) and FPN1 through a model of T-oncogene (PyMT) breast cancer in spontaneous polymerases and mining publicly available TCGA and GEO database from gene expression synthesis ( 95 ).…”
Section: Iron Metabolism In Cancermentioning
confidence: 99%
“…verified that USP35 could maintain the stability of its protein by deubiquitinating FPN1, and reduce the iron disorder triggered by erastin/RSL3, thereby promoting lung cancer cell growth and tumor progression. Meanwhile, knockdown of USP35 enhanced the sensitivity of lung cancer cells to cisplatin and paclitaxel by targeting FPN1 in lung cancer ( 94 ). However, a study showed that matrix/macrophage expression of Lcn-2 was associated with tumor onset, lung metastasis, and recurrence, whereas FPN1 was not by analyzing the expression profiles of lipocalin-2 ( Lcn-2 ) and FPN1 through a model of T-oncogene (PyMT) breast cancer in spontaneous polymerases and mining publicly available TCGA and GEO database from gene expression synthesis ( 95 ).…”
Section: Iron Metabolism In Cancermentioning
confidence: 99%
“…Several studies revealed that iron is closely associated with the development of lung cancer, and the disruption of iron homeostasis makes cells more sensitive to ferroptosis ( Kuang and Wang, 2019 ). USP35 is abundant in lung cancer cells and acts as a deubiquitinase to maintain the protein stability of ferroportin, which is a cellular efflux channel for iron ( Tang et al, 2021 ). Depletion of USP35 can promote ferroptotic cell death and sensitivity to cisplatin and paclitaxel chemotherapy in lung cancer cells ( Tang et al, 2021 ).…”
Section: Role Of Ferroptosis In Cancersmentioning
confidence: 99%
“…USP35 is abundant in lung cancer cells and acts as a deubiquitinase to maintain the protein stability of ferroportin, which is a cellular efflux channel for iron ( Tang et al, 2021 ). Depletion of USP35 can promote ferroptotic cell death and sensitivity to cisplatin and paclitaxel chemotherapy in lung cancer cells ( Tang et al, 2021 ). The iron-sulfur cluster biosynthetic enzyme NFS1 is overexpressed in well-differentiated lung adenocarcinomas and protects cells from ferroptosis within high oxygen environment by sustaining the levels of iron-sulfur cofactors ( Alvarez et al, 2017 ).…”
Section: Role Of Ferroptosis In Cancersmentioning
confidence: 99%
“…Ubiquitin‐specific protease 35 (USP35) is a deubiquitinase that is overexpressed in lung cancer, and its knockdown, in addition to promoting ferroptosis and chemotherapeutic sensitivity to cisplatin and paclitaxel, inhibits lung cancer cell growth, colony formation, and tumor progression. The mechanism by which USP35 overexpression led to ferroptosis was attributed to ferroportin (FPN) stabilization, a protein responsible for exporting iron to the outside of the cells ( Figure 3 ) ( 55 ). In the same way, a similar relationship between deubiquitinase USP11 and NRF2 was found in patients with NSCLC (SCC subtype), leading to ferroptosis resistance and cell proliferation ( Figure 3 ) ( 56 ).…”
Section: Ferroptosis Regulators In Lung Cancermentioning
confidence: 99%